Akses dalam Praktik Pemerantaraan Kesenian di Indonesia - Gita Hastarika (Antropologi Indonesia, 2021)
This article is a response to Jess C. Ribot and Nancy Lee Peluso’s theory of access through my experience working at an art brokerage agency in Indonesia. Ribot and Peluso have examined how social actors make use of resource, property, money, and people who benefit them, but they do not explain in detail how the actual process of an actor gaining an access. In my personal reflection, access turns out to be multi-layered, hierarchical, and always in the hands of other actors, never free-floating. My analysis shows that access cannot be gained for free, but is always a gift. This article explains why an actor who wants to seize access must activate his agency to accumulate capitals in the form of trust, reputation and privilege through social processes.